Nap Opportunity During the Daytime Affects Performance and Perceived Exertion in 5-m Shuttle Run Test - Boukhris, Omar; Abdessalem, Raouf; Ammar, Achraf; Hsouna, Hsen; Trabelsi, Khaled; Engel, Florian A.; Sperlich, Billy; Hill, David W.; Chtourou, Hamdi (Frontiers in Physiology, 2019)
Purpose. To compare the effect of different durations of nap opportunity during the daytime on repeated high-intensity short-duration performance and rating of perceived exertion (RPE). Methods. Seventeen physically active men (age: 21.3±3.4 y, height: 176.7±5.9 cm, body mass: 71.8±10.2 kg) performed a 5 m shuttle run test (to determine best distance (BD), total distance (TD) and fatigue index (FI)) under four conditions: a 25 min nap opportunity (N25), a 35 min nap opportunity (N35), a 45 min nap opportunity (N45) and control (no-nap) (N0). The sleep quality of each nap opportunity was evaluated using a scale ranging from 0 “no sleep” to 10 “uninterrupted, deep sleep throughout”. The four conditions were performed in a random order. RPE was recorded after each repetition of the test and the mean score was calculated. Results. BD increased after N25 (+6%) and N45 (+9%) compared to N0 (p<0.05) and was significantly higher after N45 compared to N35 (p<0.05). Compared to N0, the three nap opportunity durations enhanced TD (p<0.05) with greater enhancement after N45 compared to N25 (+8% vs. +3%) and N35 (+8% vs. +3%). For FI, no-significant differences were observed between the three nap opportunity durations and N0. The mean RPE score was significantly higher after N25 (+20%) and N0 (+19%) compared to N45 (p<0.05). All participants were able to fall asleep during each nap condition with a sleep quality score of 6.9±1.0, 7.0±0.7 and 7.1±0.8 for N25, N35 and N45. Conclusion. A nap opportunity during the daytime was beneficial for physical performance and perceived exertion with the N45 being the most effective for improving performance and reducing fatigue during the 5 m shuttle run test. The implication of the present study is that athletes might benefit from a nap opportunity of 25, 35 or 45 min before practice or before a competition.